Fibroblast growth factor 23 is associated with fractional excretion of sodium in patients with chronic kidney disease. Issue 12 (11th October 2018) - Xu, Hong; Hashem, Ali; Witasp, Anna; Mencke, Rik; Goldsmith, David; Barany, Peter; Bruchfeld, Annette; Wernerson, Annika; Carrero, Juan-Jesus; Olauson, Hannes
Abstract: Background: Recent studies suggest that the phosphaturic hormone fibroblast growth factor 23 (FGF23) is involved in regulation of renal sodium excretion and blood pressure. There is evidence of both direct effects via regulation of the sodium-chloride symporter (NCC) in the distal tubule, and indirect effects through interactions with the renin–angiotensin–aldosterone system. However, clinical data on the association between FGF23 and renal sodium regulation is lacking. Herein, we investigated the associations of FGF23 with renal sodium handling and blood pressure in non-dialysis CKD patients. Methods: This was a cross-sectional study encompassing 180 CKD patients Stage 1–5, undergoing renal biopsy. Plasma intact FGF23, 24-h urinary sodium excretion, fractional excretion of sodium (FENa) and blood pressure were measured at baseline. The association between FGF23 and renal sodium handling was explored by multivariate regression analysis. Results: The median age was 52.8 years, 60.6% were men and the median estimated glomerular filtration rate (eGFR) was 50.6 mL/min/1.73 m 2 . In univariate analysis, FGF23 was positively associated with FENa (Spearman's rho = 0.47; P < 0.001) and systolic blood pressure (rho = 0.17, P < 0.05), but not with plasma sodium, 24-h urinary sodium excretion or mean arterial blood pressure. The association between FGF23 and FENa remained significant after adjustment for potential confounders (multivariable adjusted β coefficient 0.60, P < 0.001). This association was stronger among the 107 individuals with eGFR <60 mL/min/1.73 m 2 (β = 0.47, P = 0.04) and in the 73 individuals on any diuretics (β = 0.88, P < 0.001). Adjustment for measured GFR instead of eGFR did not alter the relationship. Conclusions: FGF23 is independently associated with increased FENa in non-dialysis CKD patients. These data do not support the notion that FGF23 causes clinically significant sodium retention. Further studies are warranted to explore the mechanism underlying this association.